Does a behavioural bias affect personality traits and investors’ sentiments? : Smart PLS Model - Adel K. Khalleefah; Ahmed E. Aljedek; Tarek M. Ghomeed (African Journal of Advanced Pure and Applied Sciences, 2025)
This study investigates the influence of behavioral biases on personality traits and investors’ sentiments, focusing on overconfidence, disposition effect, anchoring, representativeness, mental accounting, emotional bias, and herding biases. Data from 753 respondents across Gujarat’s municipal corporation cities were analyzed using a Smart PLS model and structural equation modeling (SEM). Findings indicate that these biases significantly impact investors’ sentiments, with some biases, like overconfidence and disposition effect, negatively affecting sentiments, while others, like mental accounting and emotional bias, have a positive impact. Additionally, personality traits such as extraversion and openness positively influence sentiments, whereas neuroticism has a negative effect. Limitations include the sample size and reliance on self-reported data, and the study’s originality lies in its exploration of these relationships comprehensively. Practical implications suggest investors, advisors, and policymakers can benefit from understanding these dynamics to make more informed investment decisions and promote financial literacy. Overall, this research contributes to the understanding of how biases and personality traits shape investors’ sentiments, aiding in the development of strategies to mitigate irrational decision-making in financial markets.